Allozyme differentiation among populations of the Pyrenean newt Calotriton asper (Amphibia: Caudata) does not mirror their morphological diversification - Montori, Albert; Llorente, Gustavo A.; García-París, Mario (Zootaxa, 2008)
The Pyrenean newt (Calotriton asper) is a morphologically diversified species endemic to the Pyrenean mountains (Western Europe) that inhabits fast running streams and mountain lakes. Given its high morphological diversity, the species has been subdivided into at least ten different taxa, subsequently treated by most authors as local forms. Herein, we examined the electrophoretic patterns produced by 20 presumptive allozyme loci in specimens of seven populations distributed over the entire geographic range of the species. Sixteen loci were monomorphic across the sampling area and only four loci were polymorphic. No diagnostic alleles of any population or population set were detected. The average number of alleles per locus was found to be extremely low, between 1.1 and 1.2 ± 0.1. Genetic divergence among populations was minimal, with a maximum divergence of Nei 78 = 0.031. No correlation was shown between genetic and geographic distances (Mantel test: r = -0.29, t = -1.1, p = 0.13). Fst values were low, as would be expected for a nonfragmented population. Estimated gene flow among populations was high, with a Nm = 1.01. Cytochrome b mtDNA sequences from the two populations furthest apart only differed in a single position. According to these genetic/morphological discrepancies, we interpret the observed morphological diversification of C. asper as a product of rapid morphological change under local selection pressure, in response to population specific ecological conditions. The implication of our findings for conservation efforts is that we need to preserve the unique evolutionary processes occurring in single populations or small groups of populations, even if the populations involved cannot be taxonomically differentiated.